PEMBUKTIAN TINDAK PIDANA KORUPSI DI KEMENTRIAN KESEHATAN - Dina Paramitha Hefni Putri (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2017)
The aim of this research is willing to know the proof of the corruption action at theDepartment of Health.  The location is at department concerned almost in Indonesia in2016  by  taking  news  from  the  newspapers  such  as  television,  radio  and  daily newspapers local and national as well.  The results of it are (1).The corruption at the health service is very cruel and unhuman because the ill persons were being the object of it,(2). The corruptors are all any levels of the officers,(3).The way of corruption is very complicated and creative,(4). Fortunately the staffs   f the corruption staff are intelligent,(5).The officers who corrupt  cleverly are in the regional areas,(6). The sum of the corruption is fantastic.The suggestions are (1). To give the staffs in the health departments more welfare,(2).To control the projects seriously,(3).To limit the occasion for corrupting ,(4).To give tauziah to the officers.